Analysis of Consumer Trust in Direct Transaction Methods via WhatsApp in “Take on Thrift” Online Shop - Luis, Lydia Kharis; Sanjaya, Regi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to analyze the factors influencing consumer trust in direct transactions via WhatsApp at the "Take on Thrift" online shop. A descriptive approach with qualitative methods was used, collecting data through interviews and Google Form surveys from customers who had previously engaged in direct transactions via WhatsApp. The results of the study show that the factors building consumer trust in direct transaction methods via WhatsApp are seller responsiveness, buyer testimonials, direct interaction through live hosts, transparency of information, and the ease of the payment process. Although Take on Thrift's service quality was perceived as satisfactory, several areas for improvement were identified, such as increasing the number of testimonials, expanding to more social media platforms, providing earlier notifications for live sessions, switching to WhatsApp Business, and enhancing host interaction skills. This study is limited by its small sample size and focus on a single store. Future research is recommended to involve larger and more diverse samples, include multiple online stores, and conduct empirical testing on the identified trust factors.